Implementasi Budaya Sunda: Nilai-Nilai Budaya Sunda Pada Kesenian di SMP Negeri 1 Lembang - Sifa Salsabila; Silmi Zakiyah; Rima Irmayanti (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This research was conducted to determine Sundanese cultural values in SMP Negeri 1 Lembang in guidance and counseling. The background of this research is to look at the daily activities and arts carried out by students in handling Sundanese cultural values, because with the development of a more modern era so that most students and girls do not pay attention to Sundanese culture, the school applies values Sundanese cultural values in every learning activity as well as art extracurriculars at SMP Negeri 1 Lembang which is named the arts environment (LISES). We used observation, interview and documentation techniques to collect data for this study, with a total of 2 people consisting of 2 guidance and counseling teachers. To check the data validity of this study using data triangulation. Data analysis techniques according to Miles and Huberman, analysis activities consist of 4 stages, namely data collection, data reduction, data presentation, and conclusion and verification. The results of the study show that Sundanese cultural values in schools have begun to be implemented and have been running from 1999 to 2023 and have developed because there are new teachers who are competent in Sundanese culture.Â